Social behavioral changes in MPTP-treated monkey model of Parkinson's disease - Durand, Elodie; Petit, Odile; Tremblay, Léon; Zimmer, Cédric; Sgambato-Faure, Véronique; Chassain, Carine; Laurent, Marlène; Pereira, Bruno; Silberberg, Céline; Durif, Franck (Frontiers in Behavioral Neuroscience, 2015)
Parkinsonian patients experience not only the physical discomfort of motor disorders but also the considerable psychological distress caused by cognitive deficits and behavioral disorders. These two factors can result in a disruption of social relationships during the symptomatic and even the presymptomatic motor states of the disease. However, it remains difficult, if not impossible, to evaluate social relationships in presymptomatic patients. The present study focused on the evaluation of social relationships within a group of female long-tailed macaques during presymptomatic and symptomatic motor states induced by Chronic Low-Dose (CLD) and then Chronic High-Dose (CHD) systemic administration of 1-methyl-4-phenyl-l,2,3,6-tetrahydropyridine (MPTP). Dopaminergic denervation within basal ganglia and cortical areas was evaluated using Positron Emission Tomography (PET) scans with 18F-DOPA (6-[18F]-fluoro-L-3,4-dihydroxyphenylalanine) radiotracer. Interestingly, social behavioral changes could be identified in the presymptomatic motor state before any motor and/or cognitive impairment occurred. Stronger effects were observed in subordinate animals compared to dominant animals. From baseline state to CLD-presymptomatic motor state, the frequency of emitted affiliative and aggressive behaviors increased. From CLD-presymptomatic to CHD-presymptomatic motor states, the frequency of the three categories of social behaviors (aggressive, submissive and affiliative) decreased. At this time, quantitative data analysis in PET scans highlighted a dopaminergic denervation in the insula and the posterior caudate nucleus. Finally, the frequency of the three categories of social behaviors decreased during the stable-symptomatic motor state compared to baseline and presymptomatic motor states; this was also associated with motor and cognitive disorders and a dopaminergic denervation in all the evaluated cortical and subcortical structures.